2007 IEEE International Symposium on Information Theory 2007
DOI: 10.1109/isit.2007.4557400
|View full text |Cite
|
Sign up to set email alerts
|

On Ultra-Wideband MIMO Systems with 1-bit Quantized Outputs: Performance Analysis and Input Optimization

Abstract: We study the performance of multi-input multioutput (MIMO) channels with coarsely quantized outputs in the low signal-to-noise ratio (SNR) regime, where the channel is perfectly known at the receiver. This analysis is of interest in the context of Ultra-Wideband (UWB) communications from two aspects. First the available power is spread over such a large frequency band, that the power spectral density is extremely low and thus the SNR is low. Second the analogto-digital converters (ADCs) for such high bandwidth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
154
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 188 publications
(160 citation statements)
references
References 12 publications
6
154
0
Order By: Relevance
“…This shows that mono-bit ADCs may be used to save system power without an excessive degradation in performance, and confirms the significant potential of the coarsely quantized UWB MIMO channel. Using a different approach, [40] presented a similar result, and showed that the above approximation is asymptotically exact.…”
Section: Lower Bound On the Mutual Information And The Capacitymentioning
confidence: 80%
See 3 more Smart Citations
“…This shows that mono-bit ADCs may be used to save system power without an excessive degradation in performance, and confirms the significant potential of the coarsely quantized UWB MIMO channel. Using a different approach, [40] presented a similar result, and showed that the above approximation is asymptotically exact.…”
Section: Lower Bound On the Mutual Information And The Capacitymentioning
confidence: 80%
“…Therefore, the coding schemes which are needed are non-linear and -for having good performance and, at the same time, a low complexity -for instance have memory of order one. In [51][52][53], an information-theoretic framework was developed as a practical design guideline for novel codes. To this end, the following optimization has been considered in [52] …”
Section: Code-designmentioning
confidence: 99%
See 2 more Smart Citations
“…Ref. [5] analyzed the capacity using a one-bit ADC in a low SNR (Signal to Noise Ratio) regime while Ref. [6] analyzed the capacity in a high SNR regime.…”
Section: Vxdoo\ Whqv Ru Kxqguhgv Ri Dqwhqqdv Duh Frq¿jxuhgmentioning
confidence: 99%